EFEKTIVITAS PELAYANAN TRANSPORTASI PUBLIK BUS DAMRI ANGKUTAN PEMADU MODA RUTE MOJOKERTO-BANDARA JUANDA - Diana Hertati; Dynda Safitri Vandayani; Dewi Fortuna Shalsabila Ainy; Monica Dwipi Salam (Universitas Halu Oleo, 2021)
Public transportation services are service facilities that have an important and strategic position in national development. Planning and development of arrangement must be carried out in an integrated system by providing services to the community. The City Government of Mojokerto in supporting the creation of public transportation services, participates in supporting the development of the Damri Bus integrated mode of transportation made by the Surabaya Branch of Perum DAMRI. On March 21, 2020, the City Government of Mojokerto inaugurated the Moda Guide Transport (Damri) for the route of Mojokerto City - Juanda Airport. However, within one year after it was inaugurated, it was discovered that the DAMRI buses were still lacking. The purpose of this study is to empirically answer the authority of the Damri Bus Mode Guide for the Mojokerto-Juanda Airport route as a public transportation service. This research uses the method of observation and direct interviews to the field with a qualitative descriptive approach. And the data that has been obtained is then analyzed, presented in paragraph form, and conclusions. The analysis used in this study is to use the most effective theory which includes: including goals, integration, and adaptation. The results of this study indicate that the authority of public transportation services for the Damri Pemadu Bus route Mojokerto-Juanda Airport from three aspects (Achievement Objectives, Integration, and Adaptation) can be said to be effective